Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Synergistic co-culture of Monoraphidium sp. HDMA-20 and HDMA-01 to improve the efficiency of biodiesel production and flax retting wastewater treatment - Xinyi Wang; Meiqi Wang; Boqi Wang; Yimeng Lin; Wenxiang Ping (Biomass and Bioenergy, 2026)

Food-derived extracellular vesicles: an emerging intervention strategy for inflammatory bowel disease - Yimeng Wang; Yuning Zhang; Sijia Song; Juan Chen; Huiyuan Guo; Yingying Lin (Critical Reviews in Food Science and Nutrition, 2026)

Unlocking collagen-derived novel antioxidant peptides from by-product bones of silver carp: label-free peptidomic discovery, bioinformatics-aided mechanistic elucidation, and cytoprotective effects against oxidative damage - Jin Zhang; Feng Lin; Yimeng Mei; Ruoyu Xie; Jiaxin Chen; Jun Hu; Hongying Du; Guijie Hao; Shuangxi Li; Wenxuan Chen (Food Research International, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Melanoidins-derived active-N species alleviate endogenous minerals-initiated inhibitory effect during pyrolysis of waste activated sludge: Promoting methane and short-chain hydrocarbons recovery - Yimeng Jiao; Yifei Wu; Yuxin Liu; Jingqi Yuan; Zhengda Lin; Ke Wang; Yu Tian; Jun Zhang (Environmental Research, 2026)

Tropical-origin lactic acid bacteria co-fermentation enables protein network restructuring and glucose-lipid metabolic regulation in coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Xia Fan; Xin Rui; Tao Lin; Wei Li (Innovative Food Science & Emerging Technologies, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Isolation and identification of Desmodesmus sp. HDMA-07: Nutrient removal and biodiesel production potential in flax fiber wastewater - Han Wang; Xinyi Wang; Boqi Wang; Yimeng Lin; Jingping Ge; Wenxiang Ping (Process Safety and Environmental Protection, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

Covalent organic framework-mediated Nafion superhydrophobic coating for stabilizing the anode of aqueous zinc-ion batteries - Ling Zhong; Yimeng Yan; Zhixuan Ye; Xinxiang Zhang; Wenbin Yang; Jiaxian Zheng; Xiangfeng Lin; Linxin Zhang; Ge Zhou; Huiping Lin; Zhanhui Yuan (Chemical Engineering Journal, 2026)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Preparation of fish oil microcapsules for enhanced stability and controlled release via plug-and-play microfluidic chips - Peilan Xie; Zhenqian Tang; Ba Guan; Yimeng Tang; Qiyou Chen; Jiaying Ou; Kangmin Lin; Zhuo Jiang (Food and Bioproducts Processing, 2025)

Ultrasound-triggered injectable piezoelectric nanocomposite hyaluronic acid-based hydrogel for modulating inflammation and chondrogenesis in osteoarthritis treatment - Juntao Lin; Shaobing Li; Yimeng Peng; Chongyin Qiu; Mingzhao Yang; Jiayi Guo; Bo Yu; Yan Chen (Carbohydrate Polymers, 2025)

Satellite observations and hydrodynamic simulations of harmful algal blooms in Guangdong coastal waters - Xiyuan Zeng; Jianhang Zhu; Qian Chen; Xiaomin Sun; Guanxian Huang; Shaojie Sun; Bin Ai; Lin Deng; Siyu Chen; Yimeng Wang; Xi Chen; Zihao Chao; et al. (Acta Oceanologica Sinica, 2025)

Synergistic enhancement of solar interface evaporation by oxidation engineering of photothermal materials, hybridization of water channels and energy supplement of waterwheel - Yimeng Du; Jian Li; Mingfu Zhu; Pengcheng Lin; Ying Chen (Chemical Engineering Journal, 2025)

Combined oxybenzone and UVB exposure induces metabolic and neural dysregulation in Mugilogobius chulae embryos and larvae - Yimeng Wang; Jinzhi Ren; Yufei Zhao; Xiangping Nie; Ying Peng; Jin Zeng; Yuting Lin; Caixia Gao; Suqun Lai; Jianjun Li (Journal of Hazardous Materials, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Joint technique “parallel peptide synthesis & de novo sequencing” development for the structure verification and high-throughput activity screening of biological peptides from sea cucumber (Stichopus japonicus) intestinal hydrolysate - Yimeng Li; Shengfang Gao; Xiaohui Zhang; Zhuo Cao; Youyou Guo; Runkun Zhao; Yonggang Liu; Xinxin Li; Hongying Lin; Qi Qin; Bingqing Yi; Guodong Zhao (Food Research International, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

A robust Bayesian Multi-Machine learning ensemble framework for probabilistic groundwater level forecasting - Feilin Zhu; Yimeng Sun; Mingyu Han; Tiantian Hou; Yurou Zeng; Meiyan Lin; Yaqin Wang; Ping-an Zhong (Journal of Hydrology, 2025)

A data-driven model for assessing the direct coal liquefaction performance and influencing factors - Lin-Sheng Li; Hao-Wei Li; Gai-Xia Shi; Xing-Bao Wang; Yimeng Zhu; Wen-Ying Li (Fuel, 2025)

Integrative analyzing the molecular basis of Clerodendranthus spicatus aqueous extract in hyperuricemia nephropathy via network pharmacology and experimental validation - Chuang Li; Danyao Lin; Jianting Ouyang; Junyi Liu; Shouhai Wu; Delun Li; Fan Yang; Haohao Quan; Yimeng Li; Qiaoru Wu; Guirui Huang; Wei Mao (Food Bioscience, 2025)

Shade watch: Mapping citywide shade dynamics through ray tracing and LiDAR data in Hong Kong's complex 3-D built environment - Shengbiao Wu; Bin Chen; Yimeng Song; Jiafu An; Chen Lin; Peng Gong (Sustainable Cities and Society, 2025)

Isolation and characterization of high ammonium tolerant Fasciculochloris sp. HDMA-06 and its potential for nutrient removal and biodiesel production in simulated swine wastewater - Han Wang; Xinyi Wang; Jixin Liu; Yimeng Lin; Jingping Ge; Wenxiang Ping (Journal of Water Process Engineering, 2025)

International mangrove carbon sink research analysis - Youpeng Xiao; Chenglin Li; Xuxia Li; Yudong Wang; Ping Sun; Xu Xu; Haipeng Wang; Yimeng Chen; Junchuan Lin; Guisong Huang; Zhenguo Huang; Wang Xu (Regional Studies in Marine Science, 2024)

Alpha-ketoglutarate supramolecular network accelerates diabetic wound healing through exudates management and neovascularization - Yimeng Cai; Pochun Lin; Yuhan Li; Linfeng Liu; Shuqin Cao; Bin Zhao; Yueying Wang; Wei Song; Qian Wang; Xinyan Gan; Ke Xu; Qingheng Wu; et al. (Chemical Engineering Journal, 2024)

The experimental study on supercritical CO2 thermochemical reduction of eucalyptus sawdust - Yimeng Wei; Qingang Xiong; Lin Lang; Hui Jin (Fuel, 2024)

Rapid screening of prednisolone acetate adulterants in health foods using colloidal gold immunochromatographic assay - Sayed Haidar Abbas Raza; Zixin Huang; Yimeng Pang; Ruimin Zhong; Xiangmei Li; Sameer D. Pant; Lin Luo; Hongtao Lei (Chemistry and Physics of Lipids, 2024)

Immunotherapy shapes B-cell receptor repertoire to induce anti-tumor antibodies production in colon and lung cancer - Hang Su; Yimeng Wang; Sajid Khan; Yinan Huang; Zhenfei Yi; Na Zhu; Zhenghao Li; Feng Leng; Yanfen Chen; Lin Yang; Takaji Matsutani; Zhenghong Lin; et al. (Genome Instability & Disease, 2024)

Analytical solution for displacement-dependent active earth pressure considering the stiffness of cantilever retaining structure in cohesionless soil - Zhaorui Lin; Yalong Jiang; Yi Xiong; Changjie Xu; Yimeng Guo; Chao Wang; Tao Fang (Computers and Geotechnics, 2024)

Enhanced lipid productivity of Monoraphidium strains in co-cultures and their potential for biodiesel production - Yimeng Lin; Jing Xu; Jixin Liu; Han Wang; Jingping Ge; Wenxiang Ping (Algal Research, 2024)

Non-inferior solutions for virtual water strategies: Model development and a case study in northern China - Xinan Yin; Lin Yang; Ting Gao; Yimeng Liu; Zijie Gao; Yi Tan; Jiaqi Wang (Journal of Hydrology, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

Contribution of sulfur-containing precursors to release of hydrogen sulfide in sludge composting - Lin Zhu; Wei Li; Caihong Huang; Yu Tian; Beidou Xi; Weixia Wu; Yimeng Yan (Journal of Environmental Management, 2024)

Isolation and identification of Chlorella sorokiniana HDMA-16 and its cultivation potential in flax retting wastewater - Meiqi Wang; Jing Xu; Jialin Zou; Hongzhi Ling; Jingping Ge; Yimeng Lin; Wenxiang Ping (Algal Research, 2024)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

In-situ gastritis diagnosis by an oral-administration NIR fluorescent probe with a large Stokes shift and high signal-to-noise ratio - Yanyan Ma; Jie Niu; Xing Liang; Lin Wang; Yimeng Zhang; Hongmin Lv; Tao Wang; Jing Wang; Xiaonan Zhang; Shanshan Xu; Qing Zhu; Zike Jiang; et al. (Chemical Engineering Journal, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Zeolite NaP1 synthesized from municipal solid waste incineration fly ash for photocatalytic degradation of methylene blue - Qian Chen; Yimeng Zhao; Qili Qiu; Ling Long; Xiaobo Liu; Shunda Lin; Xuguang Jiang (Environmental Research, 2023)

Detection by environmental surveillance and genomic characterization of H5N8 highly pathogenic avian influenza virus from a poultry meat market in Beijing, China, 2021–22 - Shujuan Cui; Lin Zou; Yimeng Liu; Jiachen Zhao; Guilan Lu; Weixian Shi; Yang Pan; Xiaomin Peng; Daitao Zhang; Peng Yang; Quanyi Wang (Veterinary Research Communications, 2022)

Ar-plasma enhanced copper-nickel alloy catalysis for ammonia synthesis - Zhou Yimeng; Lv Jiabao; Peng Yaqi; Lin Xiaoqing; Lv Xingjie; Ye Qiulin; Liu Shaojun; Wu Angjian; Li Xiaodong (Waste Disposal & Sustainable Energy, 2022)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)